2014
DOI: 10.1155/2014/839094
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Interaction of Matrix Metalloproteinases in the Migration of Cancer Cells through Breast Tissue Stroma

Abstract: Breast cancer mortality is directly linked to metastatic spread. The metastatic cell must exhibit a complex phenotype that includes the capacity to escape from the primary tumour mass, invade the surrounding normal tissue, and penetrate into the circulation before proliferating in the parenchyma of distant organs to produce a metastasis. In the normal breast, cellular structures change cyclically in response to ovarian hormones leading to regulated cell proliferation and apoptosis. Matrix metalloproteinases (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 38 publications
0
46
0
1
Order By: Relevance
“…Cancer cell migration and invasion are promoted by a degradation of matrix collagen by metalloproteinases (20)(21)(22). In our previous paper, we reported suppression of MDA-MB-231 cell migration into type I collagen gels in the presence of galardin which is known as an MMP inhibitor (12).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cell migration and invasion are promoted by a degradation of matrix collagen by metalloproteinases (20)(21)(22). In our previous paper, we reported suppression of MDA-MB-231 cell migration into type I collagen gels in the presence of galardin which is known as an MMP inhibitor (12).…”
Section: Resultsmentioning
confidence: 99%
“…PT93 was reported as a selective MMP inhibitor, inhibiting MMP-2 and MMP-9 (22). A number of studies demonstrated that MMPs are associated with the ability of tumors to migrate and invade (12,26,27). First generation MMPIs with broad-spectrum MMP inhibitory ability cause unexpected side effects, including musculoskeletal pain and inflammation (12,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…21 Tumor cells, which grow in an uncontrolled manner, have interactions with ECM, immune system cells, and vascular tissue. 22 MMPs and other proteinases (ADAM and ADAMTS) have very important roles in cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%